2023
DOI: 10.1523/jneurosci.0962-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Hemianopia with Multisensory Training

Abstract: Hemianopia (unilateral blindness), a common consequence of stroke and trauma to visual cortex, is a debilitating disorder for which there are few treatments. Research in an animal model has suggested that visual-auditory stimulation therapy, which exploits the brain’s multisensory architecture, may be effective in restoring visual sensitivity in hemianopia. It was tested in two male human patients that were hemianopic for at least eight months following a stroke. The patients were repeatedly exposed to congrue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Case studies have shown that static, spatially and temporally correlated audiovisual stimuli displayed on computer screens can also improve perception in the blind field in adults/older adults with hemianopia after stroke, but require frequent clinic visits 49,50 . In addition, recent retrospective studies reported variable benefits of active Bevacizumab treatment on visual acuity and visual field in children with optic pathway glioma, although these improvements were often lost after discontinuation of the treatment [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Case studies have shown that static, spatially and temporally correlated audiovisual stimuli displayed on computer screens can also improve perception in the blind field in adults/older adults with hemianopia after stroke, but require frequent clinic visits 49,50 . In addition, recent retrospective studies reported variable benefits of active Bevacizumab treatment on visual acuity and visual field in children with optic pathway glioma, although these improvements were often lost after discontinuation of the treatment [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%